Synthesis of multifunction al modified particles of zerovalent iron using diazonium salts; Химия и химическая технология в XXI веке - Kurtukov V. V. Viktor Viktorovich (Химия и химическая технология на иностранном языке, 2017)
Заглавие с экрана